Changes in the Activity and Concentration of Superoxide Dismutase Isoenzymes (Cu/Zn SOD, MnSOD) in the Blood of Healthy Subjects and Patients with Acute Pancreatitis - Ściskalska, Milena; Ołdakowska, Monika; Marek, Grzegorz; Milnerowicz, Halina (Antioxidants, 2020)
This study was aimed at evaluating the changes in the concentration and activity of all superoxide dismutase isoenzymes (SOD1, SOD2, SOD3) in the blood of patients with acute pancreatitis (AP) and healthy subjects, taking into account the extracellular (plasma) and intracellular (erythrocyte lysate) compartment. The relationships between the activity/concentration of SODs, metal concentration and the markers of inflammation were evaluated. To assess the pro/antioxidative imbalance, the malonyldialdehyde (MDA) concentration and the value of total antioxidant capacity (TAC) were measured. The impact of single-nucleotide polymorphism (SNP) in the SOD1 gene (rs2070424) on the activity/concentration of SOD1 as the main isoenzyme of the SOD family was also analyzed in this study. The SOD2 activity in erythrocytes was increased compared to plasma: 10-fold in the AP patient group and 5-fold in healthy subjects. The plasma of AP patients showed an increased SOD1 concentration and decreased SOD2 and SOD3 concentrations compared to healthy subjects. The Cu/Zn SOD (SOD1 + SOD3) concentration in plasma of AP patients was elevated compared to healthy subjects, but changes in plasma Cu/Zn SOD (SOD1 + SOD3) activity in the examined groups were not observed. An influence of SNP rs2070424 in the SOD1 gene on the total activity of SOD in AP patients (with AG genotype), accompanied by an increased IL-6 concentration, was observed. In oxidative stress conditions induced by inflammation, the participation of individual forms of plasma SOD isoenzymes in total antioxidative activity of SOD changed. A significant increase in the intracellular SOD1 concentration in plasma of AP patients proves the important role of this isoenzyme in the neutralization of oxidative stress induced by impaired Cu and Zn homeostasis. The presence of increased concentration of SOD2 in erythrocytes of healthy subjects and AP patients confirms the important function of this isoenzyme in the antioxidative defense.